Study on the fluorescence of double-emission carbon quantum dots by improved intercept method. (11th January 2021) - Gao, ZhiKun; Hao, Tongfan; Fang, Qunxiang; Wu, Changchun; Zhou, Zhiping
Abstract: The fluorescence mechanism of dual-emission carbon quantum dots (DCQDs) is investigated by the improved intercept method, of which the DCQDs with high quantum yield are synthesized by hydrothermal method by using the precursor of sulfadiazine. The research of the morphology, chemical properties and fluorescence properties on DCQDs, shows that DCQDs have graphene-like structure and well-resolved lattice fringes, and that DCQDs fluorescence emission as well intensity has reversibility between acid and alkaline. Based on the ultraviolet absorption spectrum (UV–vis) of the DCQDs, the band gap of DCQDs is estimated by the improved intercept method. Then, the change law of DCQDs emission wavelength at different excitation wavelengths is studied by using the estimated band gap. It is found that the improved intercept method is well consisted with the emission change law of DCQDs at different excitation wavelengths. In addition, the influence of different concentration of Fe 3+ on the estimated band gap of DCQDs shows that the Fe 3+ has big influence on the band gap of 3.99 eV and 3.06 eV but almost no effect on band gap of 4.93 eV and 3.67 eV. It indicates that the quenching of Fe 3+ to DCQDs may be due to the band gap caused by surface defect is changed by Fe 3+ . Also, DCQDs are used as probe to detect Fe 3+ and used as spray ink. Thereby, the improved intercept method may provide a new direction for researching the fluorescence mechanism of carbon quantum dots.